The Importance of Students Perception of Online Learning During Pandemic - Fivy Andries; Fergina Lengkoan (AIBPM Publisher, 2023)
The pandemic of COVID-19 has impacted the Indonesian government through its Ministry of Education and Culture, shifting learning from classroom to online classroom. This study is a collective case study consisting of a survey analysis on students’ perceptions of online learning during the COVID-19 pandemic. A total of 83 students of the English Education Department at Universitas Negeri Manado participated in the study. Their perceptions of the online classroom were recorded through a survey, focusing on students’ participation, accessibility, material and assignment delivery, and the use of applications in online learning. The results were summarized into tables and narrative descriptions. This study identified three major struggles in conducting online learning, with nearly half of the respondents reporting negative perceptions. More than half of the students stated they experienced difficulties with online learning, such as poor internet signals, boredom, lack of interaction with friends, difficulty focusing on lessons, limited understanding of the material, and unsupportive learning environments due to living in villages or remote areas. This study may assist further related research and serve as a basis for consideration in improving and sustaining the teaching and learning process in the future without disadvantaging students, teachers, or parents.